Promotion of Values Education (Factors Involved in Prosocial Behaviors and Volunteering) - María del Carmen Olmos-Gómez; Raquel Portillo-Sánchez; Laila Mohamed-Mohand; Ligia Isabel Estrada-Vidal (MDPI AG, 2024)
(1) Background: Prosocial behavior aligns with the current societal model, where human values hold greater importance considering cultural, social, and personal variables that may influence the opportunity to benefit others. Hence, the objective of this research was established: to understand how diverse factors influence the values of young people, aiming to promote education and enhance prosocial behavior. (2) Methods: This study is quantitative research employing an empirical-analytical, cross-sectional social research method. A validated instrument was used with a sample of 1702 individuals from the city of Melilla, noteworthy for its multicultural context due to its location in North Africa. (3) Results: Inferential analysis was conducted using multiple linear regression to predict future behaviors, focusing on the factors influencing values. Various models were employed, incorporating twelve variables and four scales: sociability, transcendence, culture, and effects. (4) Conclusions: The results and conclusions suggest the need to enhance affect and sociability, primarily among the most prominent factors.